PESANTREN KESEJAHTERAAN: REKONSTRUKSI PERAN SOSIAL-EKONOMI UNTUK KEADILAN SOSIAL - Faroni, R Lukman (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2015)
Demands a stronger social role directing boarding on expanding its role to create social welfare . Welfare of the students and the community can be achieved through the optimization of leadership functions supported by a network of economic business schools . Al – Ittifaq Boarding schools realize social welfare through a system of collegial business network : kopontren as the core plasma, farmer groups , DKM , and alumni as a standalone plasma . The gift of God's power management based on high trust of the pesantren . As a source and motor of Islamic economics , thereby boarding schools can realize the prosperity that is boarding the welfare of society simultaneously .